Admission and treatment at a weekend is not associated with worse outcomes for patients admitted with fractured neck of femur. (October 2019) - Al-Ani, Asef; Bence, Matthew; Liddle, Alexander D.; Ferris, Barry
Introduction: The weekend effect is a reported phenomenon whereby patients admitted at a weekend are found to have worse outcomes than those admitted during the week. The causes are not well understood, but may have implications for the planning of medical workforces throughout the developed world. Although the magnitude of the weekend effect is reduced whenknown confounding factors are adjusted for, there are likely to be substantial residual unmeasured confounding factors. It remains unclear how much effect exists in comparable patients. The aim of this study was to determine whether the presence of a weekend effect could be detected for the patients admitted with hip fracture to our unit and to quantify this effect if detected. Methods: All hip fracture patients admitted to our unit over a five-year period were examined. All patients had their details entered onto the National Hip Fracture Database which was investigated to compare inpatient, 30-day, 120-day and 365-day mortality with specific reference to day of admission and operative treatment. Results: Two thousand one hundred and thirty fractured neck of femur patients were admitted from 2011 to 2016. We found no difference in mortality in being admitted or treated at the weekend or weekday; however, patients operated upon on a Tuesday had a statistically significant higher risk of death (OR 2.813, 95% CI 1.336–5.992, p = 0.006). The reasons for this are unclear. Conclusions: In our unit there is no evidence of a weekend effect for hip fractures.